ULAMA AND VISION 2030: SAUDI ARABIA GOVERNMENT'S STRATEGIES TO NAVIGATE A SUCCESSFUL ECONOMIC REFORM - Ulya, Nashiha; Basyar, Hamdan (Global: Jurnal Politik Internasional, 2026)
Saudi Arabia's Vision 2030 seeks to diversify its oil-dependent economy, but scepticism persists due to past reform failures, particularly in fiscal policy and labour markets. Ulama, as key figures in the Saudi "social contract," play a vital role in legitimising government policies, especially on social and religious matters. However, reforms promoting private sector growth and social liberalisation have raised concerns among conservative ulama over potential threats to Islamic values. To address this, the government under Mohammed bin Salman (MBS) employs a strategy of separating economic and religious narratives while using a "carrot and stick" approach to manage ulama opposition. This approach aligns with realism theory, emphasising economic power for national stability, and Weber's legitimacy theory, highlighting the critical role of ulama support. Without the support of religious elites (ulama), societal resistance could undermine Vision 2030's reforms.